2017
DOI: 10.5792/ksrr.16.057
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Clinical and Radiographic Outcomes of High Tibial Osteotomy in Patients with Kissing Lesions and Non-Kissing Lesions

Abstract: PurposeHigh Outerbridge grade lesions of the articular cartilage have been associated with poor outcomes of high tibial osteotomy (HTO). However, there has been no report on the efficacy of HTO in the presence of kissing lesions. The purpose of this study was to compare clinical and radiographic outcomes of HTO between kissing lesion and non-kissing lesion groups.Materials and MethodsOf the patients with medial compartment osteoarthritis and varus deformity treated with HTO between 2007 and 2012, 21 cases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Furthermore, revisions of UKA and TKA in younger patients have shown poor outcomes 12) . On the other hand, some studies have reported that HTO combined with arthroscopic microfracture in young patients with unicompartmental arthritis with kissing lesions can be effective in alleviating pain and in preserving the joint in a short-term follow-up 13 15) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, revisions of UKA and TKA in younger patients have shown poor outcomes 12) . On the other hand, some studies have reported that HTO combined with arthroscopic microfracture in young patients with unicompartmental arthritis with kissing lesions can be effective in alleviating pain and in preserving the joint in a short-term follow-up 13 15) .…”
Section: Introductionmentioning
confidence: 99%
“…Bone healing in the wedge‐gap defect was estimated based on X‐ray analyses according to the published radiological scoring system. ( 22 ) For evaluation, the defect was divided into four zones numbered from lateral to medial, as shown in Fig. 5.…”
Section: Methodsmentioning
confidence: 99%
“…(21) The sample of 20 patients (ABGS/PBO randomized in 1:1 ratio) was selected to provide 80% power to detect an average difference between ABGS and PBO of around 30% in defect healing. The bonehealing acceleration effect was estimated using X-ray analyses according to the established radiological scoring system, (16,22) and the bone mineral density (BMD), which reflected the bone formation in the defect area, was measured by CT scans using ITK-SNAP program. (16,23) This clinical model allows estimation of new bone formation within a bone defect protected by a locking plate to eliminate possible influence of mechanical stimuli.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Open wedge high tibial osteotomy (HTO) is an established procedure that provides pain relief and functional improvement in patients with medial knee osteoarthritis and varus deformities. [1][2][3][4][5][6] The biomechanical rationale of this procedure is to shift joint loading from the medial compartment, which has osteoarthritic cartilage, to the lateral compartment with relatively intact cartilage in the coronal plane. [2] The alignment change of the coronal plane could lead to unintended consequences in the sagittal and axial planes because of the three-dimensional (3-D) characteristics of the proximal tibia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The biomechanical rationale of this procedure is to shift joint loading from the medial compartment, which has osteoarthritic cartilage, to the lateral compartment with relatively intact cartilage in the coronal plane. [2] The alignment change of the coronal plane could lead to unintended consequences in the sagittal and axial planes because of the three-dimensional (3-D) characteristics of the proximal tibia. [7][8][9] The change of the posterior tibial slope in the sagittal plane, which is one of the unintended consequences of open wedge HTO, is now well known to orthopedic surgeons, and could be used as another treatment modality for knee instability by intentional control of the posterior tibial slope change.…”
Section: Introductionmentioning
confidence: 99%